Abiotic predictors and annual seasonal dynamics of Ixodes ricinus, the major disease vector of Central Europe - Daniel, Milan; Malý, Marek; Danielová, Vlasta; Kříž, Bohumír; Nuttall, Patricia (Parasites & vectors, 2015)
BACKGROUND: Abiotic conditions provide cues that drive tick questing activity. Defining these cues is critical in predicting biting risk, and in forecasting climate change impacts on tick populations. This is particularly important for Ixodes ricinus nymphs, the vector of numerous pathogens affecting humans. METHODS: A 6-year study of the questing activity of I. ricinus was conducted in Central Bohemia, Czech Republic, from 2001 to 2006. Tick numbers were determined by weekly flagging the vegetation in a defined 600 m(2) field site. After capture, ticks were released back to where they were found. Concurrent temperature data and relative humidity were collected in the microhabitat and at a nearby meteorological station. Data were analysed by regression methods. RESULTS: During 208 monitoring visits, a total of 21,623 ticks were recorded. Larvae, nymphs, and adults showed typical bimodal questing activity curves with major spring peaks and minor late summer or autumn peaks (mid-summer for males). Questing activity of nymphs and adults began with ~12 h of daylight and ceased at ~9 h daylight, at limiting temperatures close to freezing (in early spring and late autumn); questing occurred during ~70 % calendar year without cessation in summer. The co-occurrence of larvae and nymphs varied annually, ranging from 31 to 80 % of monitoring visits, and depended on the questing activity of larvae. Near-ground temperature, day length, and relative air humidity were all significant predictors of nymphal activity. For 70 % of records, near-ground temperatures measured in the microhabitat were 4-5 °C lower than those recorded by the nearby meteorological observatory, although they were strongly dependent. Inter-annual differences in seasonal numbers of nymphs reflected extreme weather events. CONCLUSIONS: Weather predictions (particularly for temperature) combined with daylight length, are good predictors of the initiation and cessation of I. ricinus nymph questing activity, and hence of the risk period to humans, in Central Europe. Co-occurrence data for larvae and nymphs support the notion of intrastadial rather than interstadial co-feeding pathogen transmission. Annual questing tick numbers recover quickly from the impact of extreme weather events.
Keywords: Seasons; Humidity; nymfa; Ixodes; Time Factors; mužské pohlaví; ženské pohlaví; zvířata; vlhkost; Nymph; Temperature; populační dynamika; Environment; časové faktory; larva; Larva; klíště; životní prostředí; Population Dynamics; Female; roční období; teplota; Male; Animals